Insect pollination of some Malaysian fruit trees with special reference to the honeybee, Apis cerana - Chum Guan, Azhar Phoon (1984)
The pollinationbi ollgyoff our common species of Malaysian fruit trees,namely the mango (Mangifera indica),the cashew (Anacardiumocc identale), the carambola (Averrhoa carambola)and the rambutan (Nepheliumlappaceum) was studied. The mango is and romnoeciousand was found to be self-compatible. Inter varietal cross -polinationusing the Malgoa variety as a pollinizer was suitable and this could be effected by Lucili asp. The cashew is also andromonoecious and is pollinated by three species of bombylid flies (viz. Ligyra sphinx, Exhyalanthrax absalon. Villa sp.) which are specially adapted to the cashew flower.